Successful Laparoscopic Hepaticojejunostomy for Infant Congenital Biliary Dilatation with both Aberrant Right Hepatic Artery and Bile Duct from the Caudate Region - Shun Onishi; Koji Yamada; Masakazu Murakami; Toshio Harumatsu; Takafumi Kawano; Satoshi Ieiri (Georg Thieme Verlag KG, 2024)
A boy with congenital hydronephrosis underwent ultrasonography every month for follow-up. At 4 months of age, ultrasonography incidentally revealed congenital biliary dilatation (5-cm type Ia). We performed laparoscopic extrahepatic bile duct resection and hepaticojejunostomy. After dissecting the dilated common bile duct (CBD), we found that the arcading-like shaped right hepatic artery (RHA) coursed in front of the CBD. Additionally, a tiny duct was identified below the main hepatic duct. At first, we thought it was a lymphatic vessel and dissected it from the main hepatic duct. However, bile flow out was recognized after dissecting the tiny duct. Finally, we confirmed it as an aberrant bile duct from the caudate region. We anastomosed the bile duct from the caudate region and main hepatic duct in a double-barrel fashion and performed hepaticojejunostomy below the RHA. The postoperative course was uneventful. Ultrasonography showed no intrahepatic ductal dilatation including the caudate lobe.